Liquidity risk and syndicate structure - Gatev, Evan; Strahan, Philip E. (Journal of Financial Economics, 2009)
We decompose syndicated loan risk into credit, market, and liquidity risk and test how these shape syndicate structure. Commercial banks dominate relative to non-banks in loan syndicates that expose lenders to liquidity risk. This dominance is most pronounced when borrowers have high levels of credit or market risk. We then tie commercial banks’ advantage in liquidity risk to access to transactions deposits by comparing investments across banks. The results suggest that risk-management considerations matter most for participants relative to lead arrangers. Links from transactions deposits to liquidity exposure, for instance, are more than 50% larger at participants than at lead arrangers.